Pengaruh Struktur Aset, Pajak Tangguhan Dan Penghindaran Pajak Terhadap Struktur Modal - Savitri, Anisa Dwi; Saputri, Sevty Wahiddirani (Universitas Pamulang, 2024)
AbstractThis research aims to analyze asset structure, deferred taxes and tax avoidance on capital structure. The type of research used is quantitative with a quantitative associative approach using secondary data. The population in this research is Consumer Non Cyclical Sector companies listed on the Indonesia Stock Exchange in 2018 - 2022. The sample used in this research was 32 companies with an observation period of 5 years in the 2018 - 2022 time period and the number of financial reports sampled in This research totaled 160. The analysis used was descriptive statistical analysis and panel data regression analysis. The analytical tool used in this research is analysis with the help of the E-views Version 12 program. The results of the research conducted show that simultaneously Asset Structure, Deferred Taxes and Tax Avoidance have an effect on Capital Structure. Meanwhile, partially Asset Structure has a positive effect on Capital Structure, Deferred Tax has no effect on Capital Structure, and Tax Avoidance has an effect on Capital Structure. Keywords: Asset Structure; Deferred Tax; Tax Avoidance; Capital Structure